Теоретичні основи формування готовності до самоосвіти майбутніх учителів початкової школи - Радюк, Інна; Radyuk, I. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Проблема формування готовності до самоосвіти майбутніх учителів початкової школи є актуальною і потребує теоретико-практичного вирішення. Метою статті є аналіз теоретичних основ процесу формування готовності до самоосвіти майбутніх учителів початкової школи, яка досягається шляхом вирішення низки завдань: розкриття сутності понять самоосвіти та готовності до самоосвіти; характеристики структурних компонентів готовності до самоосвіти та окреслення основних напрямів конструктивного розв’язання досліджуваної проблеми в контексті аналізу об’єктивно-суб’єктивних чинників формування готовності до самоосвітньої діяльності. У статті визначено, що готовність до самоосвіти є складним особистісним утворенням майбутнього вчителя початкової школи, яке формується у процесі професійної підготовки і проявляється у прагненні та здатності до самонавчання, самовиховання, саморозвитку та самовдосконалення. Важливим у формуванні готовності до самоосвіти є цілеспрямованість, системність, цілісність і неперервність. Подальшого наукового дослідження потребує розробка, обґрунтування та апробація моделі формування готовності до самоосвіти майбутніх учителів початкової школи в системі їх професійної підготовки. The problem of formation of readiness for self-education of primary school teachers is urgent and requires theoretical and practical solutions. The article is analysis of the theoretical foundations of the process of formation of readiness for self-education of primary school teachers, which is achieved by solving a series of problems: disclosure of the concepts of self and self-preparedness; characteristics of structural components of readiness for self-education and outline the main areas of constructive solution of the problem in the analysis of objective and subjective factors of formation of readiness for self education. The article stipulates that self future elementary school teacher is a complex integrative concept, which expresses the creativity and activity and student activity level of mastering the system of professional knowledge, skills formation, self-improvement. Willing to self is complicated personal formation of future elementary school teacher, which is formed during training and is manifested in the desire and capacity for self-learning, self-education, self-development and self-improvement. Formation of readiness for self-education is a complex process, the leading role which is played by a school (educational process, extracurricular training and educational activities, research work, leisure, etc.), society (media, social activities, volunteering, etc.), and the personality of the future specialist (its values, interests, needs, motivation, knowledge and skills, will, etc.). Important in the formation of preparedness is self-determination, consistency, integrity and continuity. Further research needs development, validation and test in model of readiness for self-education of primary school teachers in the system of vocational training.
Theoretical foundations of readiness for self-education of primary school teachers
Keywords: самоосвіта; готовність до самоосвіти; компоненти самоосвітньої діяльності; чинники формування готовності до самоосвіти; формування готовності до самоосвіти майбутніх учителів початкової школи; self education; readiness for self-education; self education components; factors of formation of readiness for self-education; formation of readiness for self-education of primary school teachers